The Study of Carbon Dioxide Removal in Membrane Module by Single and Mixture of Alkanolamine Aqueous Solutions - Kasim, N.; Aroua, M. K.; Sulaiman, N. M. (Journal of Applied Membrane Science & Technology, 2017)
This work presents an investigation on the performance of CO2absorption into aqueous alkanolamine solution using a hollow fiber membrane gas–liquid contactor. Aqueous solution of ethanolamine (MEA), diethanolamine (DEA), 2–amino–2–methyl–1–propanol (AMP) and piperazine anhydrous (PZ) were chosen as the absorption liquids. A microporous hollow fiber membrane made of polyvinylidene fluoride (PVDF) was used as the medium for gasliquid absorption process. In this study, the operating temperature is fixed at 30°C, while the flowrate of CO2 and alkanolamine were in the range of 1000–5000 ml/min and 50–280 ml/min respectively. The feed gas was introduced directly to the shell of the module at 1–1.5 bar and the liquid flowed through the fiber lumen side. The CO2 transfer through the membrane was found to be reaction controlled and dependent on the type of amine used. The use of piperazine as an accelerator in the mixture of the absorption liquids gives a good impact on increasing the performance for the rate of CO2 transfer.